2014
DOI: 10.1371/journal.pone.0086169
|View full text |Cite
|
Sign up to set email alerts
|

Holsteins Favor Heifers, Not Bulls: Biased Milk Production Programmed during Pregnancy as a Function of Fetal Sex

Abstract: Mammalian females pay high energetic costs for reproduction, the greatest of which is imposed by lactation. The synthesis of milk requires, in part, the mobilization of bodily reserves to nourish developing young. Numerous hypotheses have been advanced to predict how mothers will differentially invest in sons and daughters, however few studies have addressed sex-biased milk synthesis. Here we leverage the dairy cow model to investigate such phenomena. Using 2.39 million lactation records from 1.49 million dair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
97
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 88 publications
(109 reference statements)
17
97
2
1
Order By: Relevance
“…Serum protein patterns can provide information about dehydration in dairy cows during the peripartum period . Although Hinde et al (2014) reported that gestation of a daughter on the first parity increased milk production over the first two lactations, we have no data for cows in their third to fifth lactation in this study. Since dams of heifers showed a greater plasma dehydration than dams of bulls, it is possible that they also have greater milk production; however, further studies are necessary to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Serum protein patterns can provide information about dehydration in dairy cows during the peripartum period . Although Hinde et al (2014) reported that gestation of a daughter on the first parity increased milk production over the first two lactations, we have no data for cows in their third to fifth lactation in this study. Since dams of heifers showed a greater plasma dehydration than dams of bulls, it is possible that they also have greater milk production; however, further studies are necessary to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, this pattern difference could be explained by a long-term effect of fetal sex hormones on nitrogen metabolism. It is possible that male hormones divert proteins from catabolism to tissue formation in dams rather than in protein milk since lower milk yield for bulls is not compensated by higher protein and fat production (Hinde et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such responses fall out with the scope of this article, it is of note that in monotocous species, such as the cow, the fetus can influence maternal mammary development during pregnancy (e.g. fetal sex determines subsequent lactational performance of the gestating dam; Hinde et al 2014).…”
Section: Interim Conclusionmentioning
confidence: 99%
“…Also, while to the best of our knowledge, calves were managed similarly after birth regardless of reproductive technique, one cannot discount some unknown difference in management. For example, fetal sex can affect milk yield in the existing lactation (Hinde et al, 2014) and it is conceivable that sex ratio of pregnancies in first lactation varied between groups. Given that culture system affected the nature of developmental programming in mice (Fernández-Gonzalez et al, 2004;Donjacour et al, 2014;, the effect of being born using a specific reproductive technology might depend on the particular details of the techniques employed.…”
Section: Implications Of Bovine Datamentioning
confidence: 99%